2021
DOI: 10.3390/su13041607
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Sustainability Level of Crude Palm Oil Production: A Life Cycle Approach

Abstract: The Malaysian palm oil is an important source of social development and economic growth in the country. Nevertheless, it has been accused of conducting unsustainable practices that may affect the sustainability of this industry. Thus, this study aims to identify the level of sustainability of crude palm oil (CPO) production. Environmental impacts were assessed using the International Organization for Standardization (ISO) standardized life cycle assessment (LCA). Economic impacts were evaluated using life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the study from Falcone et al (2016) the conventional production scenario for vineyards was considered as the least costly and most environmentally sustainable. The production scenario with the lowest life cycle costs is not necessarily the most profitable, since there is Omran et al (2021) No specific name Line chart; bar chart often a higher selling price for organic products. The comparison of bioenergy from sources with fossil fuel is also regularly made within the LCC studies.…”
Section: Comparison Of Studiesmentioning
confidence: 99%
“…In the study from Falcone et al (2016) the conventional production scenario for vineyards was considered as the least costly and most environmentally sustainable. The production scenario with the lowest life cycle costs is not necessarily the most profitable, since there is Omran et al (2021) No specific name Line chart; bar chart often a higher selling price for organic products. The comparison of bioenergy from sources with fossil fuel is also regularly made within the LCC studies.…”
Section: Comparison Of Studiesmentioning
confidence: 99%
“…Another visualization approach using the shape of a triangle has been develo dependently in two different papers-both use the same concept of visualization Omran et al [23] follow the LCSA results and use the three sustainability dimens the three corners of the triangle (see Figure 4), Penn and Fields [24] invoke the trip tom line created by John Elkington which include the factors people, profit, and These are easily transferable to the three sustainability dimensions. Instead of profi and Fields [24] use the alternative term price which does not make a difference evaluation.…”
Section: Three-sided Trianglementioning
confidence: 99%
“…The three-sided triangle is intended to illustrate the relative balance betwe tainability dimensions and thus to identify the trend of the sustainability pe over time by regularly repeating this graphical assessment [23,24]. It is an eff proach to compare the broad picture of different alternatives and to id The three-sided triangle is intended to illustrate the relative balance between the sustainability dimensions and thus to identify the trend of the sustainability performance over time by regularly repeating this graphical assessment [23,24]. It is an effective approach to compare the broad picture of different alternatives and to identify the imbalances within the sustainability dimensions.…”
Section: Three-sided Trianglementioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, life cycle sustainability assessment is conducted to analyze the sustainability indicators of a particular product or process [2]. However, there are no studies found specifically about the sustainability of organizations.…”
Section: Introductionmentioning
confidence: 99%